The Molecular Mechanisms of Resistance to IDH Inhibitors in Acute Myeloid Leukemia - Zhuang, Xiaomei; Pei, Han Zhong; Li, Tianwen; Huang, Junbin; Guo, Yao; Zhao, Yuming; Yang, Ming; Zhang, Dengyang; Chang, Zhiguang; Zhang, Qi; Yu, Liuting; He, Chunxiao; et al. (Frontiers in Oncology, 2022)
Gain-of-function mutations of isocitrate dehydrogenases 1/2 (IDH1/2) play crucial roles in the development and progression of acute myeloid leukemia (AML), which provide promising therapeutic targets. Two small molecular inhibitors, ivosidenib and enasidenib have been approved for the treatment of IDH1- and IDH2-mutant AML, respectively. Although these inhibitors benefit patients with AML clinically, drug resistance still occurs and have become a major problem for targeted therapies of IDH-mutant AML. A number of up-to-date studies have demonstrated molecular mechanisms of resistance, providing rationales of novel therapeutic strategies targeting mutant IDH1/2. In this review, we discuss mechanisms of resistance to ivosidenib and enasidenib in patients with AML.